VOLATILITAS HARGA GANDUM DUNIA PERIODE PANDEMI COVID 19 DAN IMPLIKASINYA BAGI KETAHANAN PANGAN NASIONAL - Shaffitri, Lidya Rahma; Astari, Annisa Fauzia; Azis, Miftahul (Analisis Kebijakan Pertanian, 2024)
The COVID-19 pandemic caused price spikes in world wheat price due to restrictions imposed by major wheat exporting countries. Control to export made the world wheat price even worse. Price dynamics during the pandemic period could have negative impact on food security, especially for the world’s main wheat importing countries such as Indonesia. This study aims to estimate the volatility of world wheat price and recommend policies related to the impact of world wheat price volatility on national food security. This study used secondary data sourced from the investing.com website using close price. The data analysis method used ARCH-GARCH analysis to estimate the world wheat price volatility and qualitative analysis to provide policy recommendations through literature study. The results showed that the volatility of world wheat price during the pandemic was higher than before the pandemic. High volatility has an impact on wheat consumers in Indonesia, especially for the small and medium enterprise group and large industries. The government should design several efforts to reduce losses caused by increased wheat price volatility by diversifying food through revitalizing sorgum farming. Sorgum is one of the cereal crops that is relatively easy to cultivate because it can grow on dry and marginal land and has the same nutritional content as rice and wheat